Music in The Liturgy of The Catholic Community in Jakarta, Indonesia - Adison Adrianus Sihombing (Al-Albab, 2020)
This article discusses music in the Catholic liturgy in Jakarta, Indonesia in the postmodern era within the context of the autonomy of the Catholic Church. The Indonesian Catholic Church is an independent and autonomous church where liturgical music is a form of original artistic expression. However, in practice, the majority of Catholics in Indonesia view the liturgical celebration as uninteresting and dull. Conversely, pop music has increasingly influenced liturgical music. This reality is discussed and analyzed specifically in regards to liturgical music that experiences contextual data inference, especially in the specific cultural contexts of the community. The data analysis shows, in perception of Catholics in Jakarta, the role of liturgical music in worship is not homogeneous, but rather depends on the educational background, attention from Pastors of the Parish, cultural factors, and individual past experiences. For the most part, the level of understanding regarding the nature and important position of liturgical music in religious holy celebrations is low. Most consider that all music is the same and can therefore be used in the liturgy. Music is considered only a complement to enhance religious celebrations. In this context, the government and the Indonesian Catholic Church established the Catholic Church Choir Development Institute (LP3K) as a forum for fostering Catholics in Indonesia in the liturgical field and discussing issues related to music. This article confirms that the position of the liturgical music is crucial and has an irreplaceable significance in the liturgy, and the two are inextricably woven to each other.